Psychological interventions for refugees with depression: a systematic literature review - Cornelia Uhr; Silke Pawils; Nexhmedin Morina; Heba Alkailani; Franka Metzner (BMC Psychiatry)
Abstract Background Ongoing global crises are forcing an increasing number of people to seek refuge in other countries. Refugees have often experienced multiple potentially traumatic events before and during their flight and are burdened by psychosocial problems in exile. Epidemiological research suggests that many refugees suffer from depression and need psychological care. Yet, a systematic review of psychological interventions for refugees with depression is lacking. Method After registering in the International Prospective Register of Systematic Reviews (PROSPERO), a systematic search for trials of psychological interventions for adult refugees with depression was conducted across three electronic databases (MEDLINE, Web of Science, & PsycINFO). Relevant data reported in original journal publications were extracted, synthesized and assessed qualitatively by two independent raters. The methodological quality of included trials was assessed. Results Of 1316 publications, a total of 20 studies met eligibility criteria. Nine of these trials were carried out in an individual setting and ten in a group setting, with one of the trials being conducted digitally. Nine studies were designed as a randomized controlled trial (RCT), with only one of them using an active control group. In nine trials, the use of an interpreter was reported. Three of the trials applied multimodal treatments, and a total of sixteen studies applied manualized treatments. Seventeen interventions were adaptations of treatment programs developed in high income countries within a western context. Overall, nineteen out of twenty trials reported a significant improvement in depressive symptoms. Culturally adapted cognitive behavioural therapy (CA-CBT) was most frequently used (4 RCTs) and produced large effect sizes. Overall, all trials had limitations in study design. Conclusions Our current review suggests that psychological interventions, and in particular CA-CBT interventions, can significantly improve depressive symptoms in refugees. However, the small number of trials and limitations in study design underscore the need for more research in this field. The protocol for this review was registered in PROSPERO; registration number: CRD42021251943.